Development of Learning Media CATMOD Board (CHESSA MODIFICATION) on Straight Line Equation (PGL) Material for Class VIII SMP Nurul Imam - Fadli, Muhammad; Sulisawati, Dwi Noviani; Hidayatin, Nur (International Journal of Trends in Mathematics Education Research, 2025)
One of the activities that helps the teaching and learning process (KBM) is the process of providing interesting practice questions, one of which is with educational games. This research is development research that aims to produce valid, effective, and practical learning media. This research is development research, or research and development (RD), with the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation. The resulting product is CATMOD (Modified Chess), a medium that is basically chess, then designed to be used as a learning medium, especially for linear equation material. CATMOD has been declared valid from the material aspect and the learning media aspect with consecutive scores of "4.33" and "4.14," both of which are included in the valid category. CATMOD has been tested on class VIII A Nurul Imam Randuagung students and produced a practicality index of use of "2.7," which is included in the good category. Furthermore, the posttest test with an average of 90.2 showed that there was an increase in student learning outcomes from before and after using the media. Based on these three results, it can be concluded that this medium is valid, practical, and effective.